A facile method to synthesise unique Si nanostructure materials by non‐through‐hole anodic alumina templating. (27th November 2012) - Liang, Ying; Wang, Xiao Dan; Liu, Ning; Huang, Ju
ABSTRACT A facile method was proposed to synthesise unique one‐dimensional Si quasi‐belt nanomaterials using non‐through‐hole anodic alumina membranes (AAMs) templating. Combined with the chemical vapor deposition technique, silane gas reacted with the AgNO3 solution within AAM pores. The morphology of the resulting Si nanomaterials was characterised by scanning electron microscopy, transmission electron microscopy, Raman, and photoluminescence experiments. The results indicated the formation of quasi‐belt structures composed of small grains. The synthesis mechanism was also analysed. Copyright © 2012 John Wiley & Sons, Ltd.